2024
DOI: 10.1007/s12017-023-08771-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-Week Naringin Supplementation on Neurogenesis and BDNF Levels in Ischemia–Reperfusion Model of Rats

Esen Yilmaz,
Gozde Acar,
Ummugulsum Onal
et al.

Abstract: Background: Ischemic stroke is the leading cause of mortality and disability worldwide with more than half of survivors living with serious neurological sequelae; thus, it has recently attracted a lot of attention in the field of medical study. Purpose: The aim of this study was to determine the effect of naringin supplementation on neurogenesis and brain-derived neurotrophic factor (BDNF) levels in the brain in experimental brain ischemia–reperfusion. Study design: The research was carried out on 40 male Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…However, similarly to what was observed above in a more recent study carried out with the Flavonol Galangin [89], the beneficial effect of Naringin could also be related to the neurotrophic activity that this bioactive compound is able to exert. This finding is also in agreement with what was recently observed by Yilmaz et al [125] in an ischemia-reperfusion animal model, which showed that Naringin was able to revert impaired neurogenesis to normal and increase the levels of BDFN in the HIP and frontal cortex of the animals.…”
Section: Flavonoids and Dox-induced Chemobrainsupporting
confidence: 93%
“…However, similarly to what was observed above in a more recent study carried out with the Flavonol Galangin [89], the beneficial effect of Naringin could also be related to the neurotrophic activity that this bioactive compound is able to exert. This finding is also in agreement with what was recently observed by Yilmaz et al [125] in an ischemia-reperfusion animal model, which showed that Naringin was able to revert impaired neurogenesis to normal and increase the levels of BDFN in the HIP and frontal cortex of the animals.…”
Section: Flavonoids and Dox-induced Chemobrainsupporting
confidence: 93%